2022
DOI: 10.31234/osf.io/5w9yf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From outcome-based to language-based preferences

Abstract: We review the literature on models that try to explain human behavior in social interactions described by normal-form games with monetary payoffs. We start by covering social and moral preferences. We then focus on the growing body of research showing that people react to the language in which actions are described, especially when it activates moral concerns. We conclude by arguing that behavioral economics is in the midst of a paradigm shift towards language-based preferences, which will require an explorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 140 publications
1
20
0
Order By: Relevance
“…Therefore, there existed differences in the language structure among the gratitude letters of the three groups. To eliminate the influence of language structure (Capraro et al, 2022 ), the current research adopted consistent linguistic expressions on the gratitude letters of the three groups in study 4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, there existed differences in the language structure among the gratitude letters of the three groups. To eliminate the influence of language structure (Capraro et al, 2022 ), the current research adopted consistent linguistic expressions on the gratitude letters of the three groups in study 4.…”
Section: Resultsmentioning
confidence: 99%
“…Study 4 adopted consistent linguistic expressions on the gratitude letters of the three groups (other-focused, self-focused, control) to eliminate the influence of language structure (Capraro et al, 2022 ) in a real donation context. Study 4 also used subsequent donation amount (the average, ¥) as the dependent variable to improve the internal validity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Language is a powerful tool shaping various aspects of human behaviour [1][2][3][4] . For instance, recent research found that moral frames-i.e., language cues emphasizing moral aspects of decisions and behaviours-encourage people to act in a prosocial way [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%